Analysis of the Understanding and Application of Islamic Religious Values among Islamic Religious Education Students - Sari, Dila Puspita; Rahmadani, Jalwa Suci; Amri, Khairul (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This research aims to analyze the understanding and application of religious teaching values in Islamic religious education among students. Qualitative research methods were used by conducting interviews and observations of PAI students at Muhammadiyah University, North Sumatra. The results of the questionnaire show that the majority of students have a good understanding of Islamic values, but there is still room for further improvement in understanding. The majority of students consider it important to apply Islamic values in everyday life and feel significant benefits from implementing these values. Challenges in implementing Islamic values include internal and external challenges, but students actively seek solutions and support to overcome these challenges. It is hoped that the results of this research will provide additional insights and relevant solutions to increase the application of Islamic values among students, with the aim of providing benefits to individuals, educational institutions and society as a whole.